1986
DOI: 10.1093/schbul/12.2.173
|View full text |Cite
|
Sign up to set email alerts
|

Season of Birth: Schizophernia and Bipolar Disorder

Abstract: Studies investigating the association between the risk of schizophrenia and season of birth are reviewed and the association clearly established. This association cannot be explained on the basis of age-incidence or age-prevalence artifacts. Other studies suggest there may be an association between bipolar disorder and season of birth. The leading theory in explaining the season of birth phenomenon is that a seasonal factor (such as viral infection, malnutrition, vitamin deficiency, prenatal or obstetrical com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
94
0
5

Year Published

1993
1993
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(105 citation statements)
references
References 53 publications
6
94
0
5
Order By: Relevance
“…A connection has been made between schizophrenia and winter birth. Evidence for this comes from studies in both the northern and southern hemispheres including Oceania (Boyd et al, 1986;McGrath and Welham, 1999). If this disease is influenced by maternal nutrient intake, we speculate that the period of fetal risk is most likely the last months of brain development before birth when folate intake levels are low, and not the embryonic and early fetal period when the gross structure of the central nervous system is developing as nutrient intake levels are at their highest at this stage.…”
Section: Winter Birth and Schizophreniamentioning
confidence: 92%
See 1 more Smart Citation
“…A connection has been made between schizophrenia and winter birth. Evidence for this comes from studies in both the northern and southern hemispheres including Oceania (Boyd et al, 1986;McGrath and Welham, 1999). If this disease is influenced by maternal nutrient intake, we speculate that the period of fetal risk is most likely the last months of brain development before birth when folate intake levels are low, and not the embryonic and early fetal period when the gross structure of the central nervous system is developing as nutrient intake levels are at their highest at this stage.…”
Section: Winter Birth and Schizophreniamentioning
confidence: 92%
“…There is substantial evidence associating winter birth with increased risk of non-deficit or type I schizophrenia, which makes up around 85% of cases (Boyd et al, 1986;Gallagher et al, 1999;McGrath and Welham, 1999;Mortenson et al, 1999;Messias et al, 2004). There is some evidence that those born autumn have the lowest risk of developing multiple sclerosis, whereas those born in spring have an increased risk (James, 1995;Willer et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has reported a statistically significant influence of season of birth on factors such as brain tumour development 1 , handedness 2 , longevity 3 , personality 4 , and schizophrenia and bipolar disorder 5 . Does season of birth also have an influence on mood?…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years birth patterns of patients with organic and psychiatric disorders have been studied extensively (e.g., Boyd, Pulver, & Stewart, 1986;Dalèn, 1975). The rationale behind this research is as follows: identifying specific birth patterns for disorders may lead to the detection of seasonal environmental factors that contribute to the etiology of these disorders (see Barak, Ring, Sulkes, Gabbay, & Elizur, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Schizophrenia is a case in point. It has been found consistently that the incidence of schizophrenia is higher in persons born in the winter months than in those born during the rest of the year (e.g., Boyd et al, 1986;McGrath, Welham, & Pemberton;1995). Seasonality phenomena have also been reported for patients with congenital disorders such as Down syndrome (Harlap, 1974;Jongbloet & Vrieze, Relatively few studies have looked at birth patterns of autistic patients.…”
Section: Introductionmentioning
confidence: 99%